Climate quiz: a web application for eliciting and validating knowledge from social networks - Scharl, Arno; Sabou, Marta; Föls, Michael (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
With more than 800 million monthly active users, Facebook bears significant potential for science projects. Climate Quiz is an interactive Web application in the tradition of "games with a purpose" that leverages this potential to create metadata through a crowdsourcing-based approach. It presents participants with two types of challenges: (1) selecting the correct relation to connect two environmental concepts, and (2) answering climate-related multiple choice questions. Climate Quiz aims to create shared meaning through collaborative ontology building, a process that captures emergent semantics and elicits formal knowledge in the form of a domain model. As an innovative survey instrument, the application leverages social networking platforms to capture indicators of environmental attitudes, lifestyles and behaviors.